2011
DOI: 10.1089/ast.2010.0562
|View full text |Cite
|
Sign up to set email alerts
|

Lava Cave Microbial Communities Within Mats and Secondary Mineral Deposits: Implications for Life Detection on Other Planets

Abstract: Lava caves contain a wealth of yellow, white, pink, tan, and gold-colored microbial mats; but in addition to these clearly biological mats, there are many secondary mineral deposits that are nonbiological in appearance. Secondary mineral deposits examined include an amorphous copper-silicate deposit (Hawai'i) that is blue-green in color and contains reticulated and fuzzy filament morphologies. In the Azores, lava tubes contain iron-oxide formations, a soft ooze-like coating, and pink hexagons on basaltic glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
138
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(150 citation statements)
references
References 68 publications
11
138
0
1
Order By: Relevance
“…This indicates that the filaments are composed of carbon (likely organic matter) and not replaced by calcite. Noting that these pool fingers were active in the cave prior to sampling and treatment, we conclude that the filaments must be microbial filaments, confirming the interpretation of Melim et al (2008), Jones (2009Jones ( , 2010Jones ( , 2011, Northup et al (2011), and Miller et al (2012, 2014 that reticulated filaments are an unknown microbe. Ongoing research by our team is working to identify this microbe.…”
Section: Reticulated Filamentssupporting
confidence: 88%
See 2 more Smart Citations
“…This indicates that the filaments are composed of carbon (likely organic matter) and not replaced by calcite. Noting that these pool fingers were active in the cave prior to sampling and treatment, we conclude that the filaments must be microbial filaments, confirming the interpretation of Melim et al (2008), Jones (2009Jones ( , 2010Jones ( , 2011, Northup et al (2011), and Miller et al (2012, 2014 that reticulated filaments are an unknown microbe. Ongoing research by our team is working to identify this microbe.…”
Section: Reticulated Filamentssupporting
confidence: 88%
“…Jones (2009Jones ( , 2010Jones ( , 2011 reported on calcitized examples from cave pearls, terrestrial oncoids, and stalactites from the Cayman Islands. Northup et al (2011) identified reticulated filaments from a copper-silicate stalactite in a Hawaiian lava cave. Miller et al (2012) found Mnmineralized reticulated filaments in a granite water tunnel near Oporto, Portugal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speleothems in lava tubes generally consist of siliceous minerals owing to the mineralogy and chemical composition of the host basalts [30,31]. Nevertheless, calcium carbonate or calcium sulfate minerals (in the form of calcite or gypsum, respectively) have been reported on the walls and ceilings of lava tubes [32][33][34]. For instance, the internal structure of many cave corals, or coralloids, found in lava tube caves shows deposition layers with different mineralogical compositions, alternating between siliceous and carbonate minerals [27,35].…”
Section: Applied Gas Chromatography Coupled To Isotope Ratio Mass Spementioning
confidence: 99%
“…국외에서 는 동굴지역의 다양한 물리화학적 환경으로 인해 발생하는 독특 한 미생물 생태계에 대해서 보고되고 있다 (Chen et al, 2009;Tetu et al, 2013). 특히 미생물의 에너지원으로 작용하는 물질 들인 환원된 황 및 질소(H2S, NH3) 등이 존재하는 지역은 화학 무기영양(Chemolithotroph) 세균에 의해 생태계의 일차생산이 일어나는 독특한 미생물 생태계가 생성되기도 한다 (Northup et al, 2011;Borsodi et al, 2012;Tetu et al, 2013). filteration)을 통해 PCR 저해 물질을 제거하고 최종적으로 세균 및 고세균의 16S rRNA 유전자 증폭에 이용하였다.…”
unclassified